The entomological exhibition of a Science museum and its contributions to non-formal Education - Ribeiro, Nathália Cristina Gonzalez; Sant’Ana, Débora de Mello Gonçales (Acta Scientiarum. Biological Sciences, 2019)
The Insecta Class is the most diverse group of animals on the planet. A big part of this composition is available in the collections of Natural History Museums, being essential for researches and diffusion actions involving a specialized and lay public. This paper aimed to verify the importance of an entomological exhibition of a Science museum for the acquisition of new knowledge and conception change regarding insects. To this end, 128 fourth-graders from elementary school were asked to draw an insect and write a brief description of it in relation to their knowledge about insects. Then, they visited an entomological exhibition, and a week later, using the "stimulated recollection method", they made a new drawing and description. The extracted data were organized in categories and statistically analyzed. Significant changes were observe regarding the children’s knowledge and concepts on insects in most of the analyzed aspects, such as the decrease of drawings and descriptions of animals belonging to other taxonomic groups and an increase on correct descriptions of concepts.